PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NET PROFIT MARGIN (NPM) PADA PT. KIMIA FARMA TBK PERIODE 2013-2022 - Indriani Millenia, Hilda; Astuti, Widia (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of current ratio (CR) and Debt to Equity Ratio (DER) on Net Profit Margin (NPM) at PT. Kimia Farma Tbk Period 2013- 2022. The population of this research is all financial reports PT. Kimia Farma Tbk. The sampling method used was a purposive sampling method, so that samples were obtained for 10 years of observation. Research data was obtained from the company website and the samples used are balance sheets and profit and loss reports from PT. Kimia Farma. The sample data analysis technique used is multiple linear regression analysis with the SPSS version 25 program and the collection technique is purposive sampling. The results of this research show that partially the Current Ratio variable has a significant effect on Net Profit Margin where the T-count is greater than the T-table (5.581 > 2.36462) and the significance value is smaller than 0.05 (0.001 < 0.05). The Debt to Equity Ratio variable has a significant effect on Net Profit Margin where the T-count is greater than the T-table (3.342 > 2.36462) and the significance value is smaller than 0.05 (0.014 < 0.05). Based on the results of the F test it shows that simultaneously Current Ratio (CR) and Debt to Equity Ratio (DER) where F-count is (21.118) > F- table is (4.74) and obtained a significance (F-statistic) of 0.001 which is smaller than 0.05 . Based on the results of the coefficient of determination (R²) which obtained a value of 1.05210, this explains that the influence of the presentation of the independent variable on the dependent variable is 85.20% and the remaining 14,20% is influenced by other factors outside the variables of this research.